La Gestión Financiera y la Rentabilidad en la empresa Biomax en la época del covid19. - Sánchez Cruz, Doris Dayan (2022)
The objective of this present research was to know the contribution of financial management to the profitability of Biomax company in the covid period. The methodology used in the study is the hypothetical deductive method through bibliographic research. The economic analysis of the financial statements of the company was performed using the Excel tool to obtain important information on financial management and profitability; it also made use of the interview technique applied to the manager of the company Biomax, usinf research tools such as an interview and an observation sheet to verify the accounting documents. The results showed that financial management affects the profitability of the company Biomax and in the economic field by using and applying one of the financial tools such as ratios, thus assessing and showing the situation of the company in the years 2019-2020, indicating that if there are changes unlike past years due to the pandemic since various restrictions arose that affected all labor sectors, did not allow the activities to perform typically, thus causing havoc in the balance sheets, as a conclusion it is determined that the company should embrace some strategies raised and decrease the level of leverage to improve its level of profitability.